Ethanol on Port Fuel Injection Engine in Motorcycle Engine - Srirugsa, Tanawat; Wongklang, Wittaya; Eiadtrong, Suppakit; Srichai, Prathan (Princess of Naradhiwas University Journal, 2021)
A study of pure ethanol (99.5%) was used as fuel in a 4-stroke single-cylinder on port fuel injection engine of displacement volume 125 cc. Ethanol blended with gasoline at a ratio (v/v %) of 10%, 85%, and pure ethanol tested in 4 conditions was conducted in experimental conditions, E10, E85, E100, and E100C. However, the compression ratio of the combustion chamber was increased only in E100C condition. It was found that the engine power was proportional with the increased ethanol blending ratio; the E100C condition had higher power than E10 approximately 12.18%. The brake-specific fuel consumption (BSFC) of E85, E100, and E100C conditions were higher than E10 approximately 18.26%, 33.34%, and 27.45%, respectively. The brake-specific energy consumption (BSEC) at E85, E100, and E100C conditions were less than E10 approximately 13.43%, 11.00%, and 14.93%, respectively. The exhaust emissions of E85, E100, and E100C conditions had less carbon dioxide (CO) than E10 about 21.14%, 29.53%, and 10.67%, respectively, and had nitrogen oxide (NOx) lower than E10 about 29.22%, 51.28, and 51.16%, respectively. The unburned hydrocarbon (HC) at E85 and E100C were less than E10 about 22.78% and 32.44% but the E100 condition was higher than E10 about 9.11%. Finally, the exhaust temperature at E85, E100, and E100C conditions was less than E10 approximately 5.97%, 3.40%, and 5.09%, respectively.